A novel method of interference source direction-finding with an existing single antenna beam in communication satellites - Ma, Dingkun; Li, Hao; Wu, Ruixue; Li, Yinan; Lü, Rongchuan; Ma, Yan; Ding, Yi; Yang, Xiaojiao; Jiang, Tong; Yu, Xumin (Frontiers in Physics, 2023)
Interference has recently become a critical factor in communication satellite performance, and the interference source location is one of the most important factors in resolving this issue. The article proposes an innovative method of interference source direction-finding suitable for communication satellites with an existing single antenna beam and single radio frequency (RF) channel, which utilizes the symmetry of the antenna pattern to search for interference sources. Compared to traditional position methods with time-frequency-synchronized multi-satellites or a directing antenna array in a single satellite, the method does not require any particular direction-finding payload in communication satellites and shares existing antennas and RF channels with communication systems in satellites. The ability to find the direction of the interference source is a software-defined function in the communication processor. The proposed method provides a novel way to solve the problems of interference source direction-finding with the least engineering complexity, and it has excellent coexistence with other existing systems in communication satellites. The computer simulation and out-field experiment results in this article show that the method has excellent performance with high direction-finding resolution within extensive coverage, offering significant value and bright prospects for resolving the growing interference issues in communication satellites.